BS EN IEC 62271-200 AMD1. High-voltage switchgear and controlgear. Part 200. AC metal-enclosed switchgear and controlgear for rated voltages above 1 kV and up to and including 52 kV (10th June 2022) - British Standards Institution,
No abstract available